Religious Trauma Syndrome (RTS): Examining the Origins of Trauma in Religious Practice and Pathways to Recovery - Ma'rief, Muammar Iqbal; Sukmawati, Relung Fajar (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
Religious Trauma Syndrome (RTS) has gained increasing scholarly and clinical attention as reports of psychological and spiritual distress linked to religious environments emerge across diverse contexts worldwide. Introduced by Marlene Winell, RTS refers to symptoms such as guilt, shame, fear of divine punishment, anxiety, and depression that persist beyond the individual’s departure from a religious community. This study seeks to examine the root causes of RTS through a qualitative library research approach, drawing on Winell’s work and recent studies within the past five years. Findings suggest that trauma is more often generated by the interpretation and enforcement of doctrine rather than by religious teachings themselves. Four major contributing factors were identified: pathological altruism, spiritual abuse, fear-inducing dogmatism, and exclusive community pressure. By distinguishing religion as a value system from harmful practices, this study contributes theoretically to the conceptual understanding of RTS and practically to therapeutic, educational, and communal strategies for creating spiritually safe environments.